Electrically tunable all-dielectric optical metasurfaces based on liquid crystals - Komar, Andrei; Fang, Zheng; Bohn, Justus; Sautter, Jurgen; Decker, Manuel; Miroshnichenko, Andrey; Pertsch, Thomas; Brener, Igal; Kivshar, Yuri S.; Staude, Isabelle; Neshev, Dragomir N. (Applied Physics Letters, 2017)
We demonstrate electrical tuning of the spectral response of a Mie-resonant dielectric metasurface consisting of silicon nanodisks embedded into liquid crystals. We use the reorientation of nematic liquid crystals in a moderate applied electric field to alter the anisotropic permittivity tensor around the metasurface. By switching a control voltage “on” and “off,” we induce a large spectral shift of the metasurface resonances, resulting in an absolute transmission modulation of up to 75%. Our experimental demonstration of voltage control of dielectric metasurfaces paves the way for new types of electrically tunable metadevices, including dynamic displays and holograms.
CRIS-Team Scopus Importer:2023-04-20